Zeolites ameliorate asbestos toxicity in a transgenic model of malignant mesothelioma. Issue 9 (22nd August 2019) - Fan, Xiyong; McLaughlin, Chris; Robinson, Cleo; Ravasini, Jason; Schelch, Karin; Johnson, Thomas; van Zandwijk, Nico; Reid, Glen; George, Anthony M.
Abstract: Malignant mesothelioma (MM) is an almost invariably fatal cancer caused by asbestos exposure. The toxicity of asbestos fibers is related to their physicochemical properties and the generation of free radicals. We set up a pilot study to investigate the potential of the zeolite clinoptilolite to counteract the asbestos carcinogenesis by preventing the generation of reactive nitrogen and oxygen radicals. In cell culture experiments, clinoptilolite prevented asbestos‐induced cell death, reactive oxygen species production, DNA degradation, and overexpression of genes known to be up‐regulated by asbestos. In an asbestos‐induced transgenic mouse model of MM, mice were injected intraperitoneal injections with blue asbestos, with or without clinoptilolite, and monitored for 30 weeks. By the end of the trial all 13 mice injected with asbestos alone had reached humane end points, whereas only 7 of 29 mice receiving crocidolite and clinoptilolite reached a similar stage of disease. Post‐mortem examination revealed pinpoint mesothelioma‐like tumors in affected mice, and the absence of tumor formation in surviving mice. Interestingly, the macrophage clearance system, which was largely suppressed in asbestos‐treated mice, exhibited evidence of increased phagocytosis in mice treated with asbestos and clinoptilolite. Our study suggests that inhibiting the asbestos‐induced generation of reactive oxygen species and stimulating the macrophage system may represent a pathway to amelioration of asbestos‐induced toxicity. Additional studies are warranted to explore the underlying mechanisms responsible for our observations.